MODEL PENGENDALIAN SOSIAL PELANGGARAN DISIPLIN SEKOLAH DI SMA NEGERI 8 PONTIANAK - Partiwi, Sri Uji (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to obtain information about the social control model for the violation of school discipline in SMA Negeri 8 Pontianak. This study is a descriptive with the qualitative approach. The location of this study is SMA Negeri 8 Pontianak. Sources of data in this study is the principal, three teachers and four students. Data obtained through in-depth interviews, observation and documentation. Data analysis was performed through the third flow of activities of data reduction, data presentation, and data verification. Data validity checking is done through triangulation, member check and perform detailed description. The results of data analysis concluded: (1) The purpose of social control for the violation of school discipline in SMA 8 Pontianak is combined goal which is to prevent the violation of school discipline while restoring irregularities that are not in accordance with the rules of school discipline (repressive), (2) The way of social control for the violation of school discipline in SMA 8 Pontianak using persuasive non-violent approach and be formal and informal, (3) The pattern of social control for the violation of school discipline in SMA 8 Pontianak dominant group to its members. While other patterns are used based on the needs or problems of social deviations that occur. Â  Keywords: Social control, violation, school discipline